SURVIVAL ANALYSIS TO DETERMINE AGE TO GIVE FIRST BIRTH IN WOMEN IN EAST JAVA USING EXTENDED COX REGRESSION - Santi Wulan Purnami; Fitria Nur Aida; Sutikno Sutikno; Diyah Herowati; Achmad Sjafii; Siska P Wibisono; Ayu Mayliawati (Universitas Airlangga, 2021)
The age of a woman when giving birth to her first child needs to be a concern because it is related to the safety of the mother and baby. A woman being too young or too old increases the risk of death for both the mother and baby. Every woman giving birth for the first time is likely to experience psychological disorders such as anxiety and excessive fear during labor, and even postpartum depression. Given the importance and possible extent of the consequences of women giving birth for the first time, this study intended to assess the factors that influence the age at first birth, especially amongst women of childbearing age in East Java. These factors include the age at first marriage, education, and region. The method used was the extended Cox regression model. The analysis shows that the age at first marriage and education are factors that significantly influence the age at first birth. The more mature the age at first marriage, the more mature the age at first birth. Likewise, the higher the educational status, the higher the potential for giving birth to a first child over the age of 23, especially amongst women who graduated high school and university.